2019
DOI: 10.1111/jcmm.14130
|View full text |Cite
|
Sign up to set email alerts
|

Ursolic acid prevents doxorubicin‐induced cardiac toxicity in mice through eNOS activation and inhibition of eNOS uncoupling

Abstract: In addition to the known antitumour effects of ursolic acid (UA), increasing evidence indicates that this molecule plays a role in cardiac protection. In this study, the effects of ursolic acid on the heart in mice treated with doxorubicin (DOX) were assessed. The results showed that ursolic acid improved left ventrical fractional shortening (LVFS) and left ventrical ejection fraction (LVEF) of the heart, increased nitrogen oxide (NO) levels, inhibited reactive oxygen species (ROS) production and decreased car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 35 publications
(68 reference statements)
1
24
0
Order By: Relevance
“…LVEF and LVFS values of each group were also analyzed. For Sham group, the LVEF and LVFS were 71.1 ± 7.4% and 40.0 ± 6.3%, respectively at 7th day after MI, which were quite close to the heart function of normal mice as reported by other groups [ 56 , 57 ]. At 28th day after surgery, the hydrogel contained VEGF or/and BMP9 were significantly increase compared with PBS group or Gel group; the LVEF showed the highest in Gel + B/SF + V compared with the other hydrogels.…”
Section: Resultssupporting
confidence: 84%
“…LVEF and LVFS values of each group were also analyzed. For Sham group, the LVEF and LVFS were 71.1 ± 7.4% and 40.0 ± 6.3%, respectively at 7th day after MI, which were quite close to the heart function of normal mice as reported by other groups [ 56 , 57 ]. At 28th day after surgery, the hydrogel contained VEGF or/and BMP9 were significantly increase compared with PBS group or Gel group; the LVEF showed the highest in Gel + B/SF + V compared with the other hydrogels.…”
Section: Resultssupporting
confidence: 84%
“…Many inhibitors and agonists have been found to have satisfactory therapeutic effects. For example, ursolic acid, which has an anti-tumor effect, has been proven to promote NOS3 phosphorylation and inhibit NOS3 uncoupling, thereby preventing doxorubicin-induced cardiac toxicity ( 50 ). However, the research on and application of NOS3 -targeted medicine in malignant tumors are still extremely limited.…”
Section: Discussionmentioning
confidence: 99%
“…Ser-1177 on eNOS, phosphorylation of a COOH-terminal Akt/PKBdependent phosphorylation site, will displace the regulatory COOH-terminal tail to relieve repression of NO synthesis (Balligand et al, 2009). Recently, researchers have a further understanding of the effects of Dox on the phosphorylation of eNOS: Dox can further affect the formation of monomer/dimer ratio of eNOS by influencing BRCA1, ALDH2, NOX4, etc., or Ang II receptor, regulating Akt and other signal pathways, which can result in eNOS uncoupling, inhibit the phosphorylation of eNOS and catalyze the biological synthesis of NO (Singh et al, 2013;Ge et al, 2016;Octavia et al, 2017;Toedebusch et al, 2018;Mu et al, 2019). However, the redox crosstalk of superoxide/hydrogen peroxide produced by mitochondria with other ROS producing enzymes such as NADPH oxidases are also of outstanding importance, which further induces eNOS uncoupling (Deng et al, 2007;Daiber, 2010;Kröller-Schön et al, 2014;Daiber et al, 2017a).…”
Section: Discussionmentioning
confidence: 99%
“…At present, strategies to increase the bioavailability of NO in VE have been proven to contribute to endothelial protection. For example, ginsenoside Rg3 (Wang et al, 2015), Ursolic acid (Mu et al, 2019), vanilloid 1 (Ge et al, 2016), fidarestat (Sonowal et al, 2018), Folic acid (Octavia et al, 2017), zofenoprilat (Monti et al, 2013) can upregulate eNOS expression and phosphorylation, enhance its activity, ultimately remove NO deficit and restore the NO bioavailability. In vivo and in vitro, our data after Dox-treated have shown that with the increase of ROS generation, and endothelial dysfunction, eNOS expression decreased, especially eNOS phosphory-lation, and thereby NO content decreased.…”
Section: Discussionmentioning
confidence: 99%